ACADEMIC STRESS AND COPING SELF-EFFICACY OF SENIOR HIGH SCHOOL STUDENTS ATTENDING DISTANCE LEARNING DURING SARS-COV-2 PANDEMIC (Malaysian Journal of Learning and Instruction, 2024)
Purpose – Throughout the high school years, especially for senior high school (SHS) level, academic stress emerges as the prevalentpsychological state among students, particularly due to the simultaneous occurrence of adolescence and the increased intensityof academic obligations and responsibilities that must be fulfilled during this stage. As they approach college, they face the addedpressure of making important career-related choices, which further intensifies the challenges they encounter during this phase. Withclasses transitioning to online platforms as an alternative measure for schools during the SARS-CoV-2 outbreak in the Philippines, presented numerous challenges and difficulties, it is crucial to examine the academic stress and coping self-efficacy among SHS students during this transition period. Additionally, this study aimed to investigate the predictors of academic stress and coping self-efficacy utilizing the sociodemographic profile of the participants.Methodology – A descriptive research design was employed in the study. A total of 446 SHS students from Grade 11 to Grade 12 in one of the academic institutions in Quezon City were purposively selected to participate by answering two self-administered online measures on academic stress (Educational Stress Scale for Adolescents) and coping self-efficacy (Coping Self-Efficacy Scale). The collected data analyzed using SPSS v25.Findings – Results revealed that self-expectation (M = 3.65) and workload (M = 3.45) are the primary sources of academic stress, andSHS students are more confident utilizing problem-solving (M = 6.17) to cope with academic stress. Further, being female (P= 0.01), level (P = 0.08), and belonging to the HUMSS (Humanities and Social Sciences) strand (P = .08) increase stress scores. A significant negative correlation of -0.26 (95% CI:-0.35, -0.17) between stress and coping self-efficacy was also found, which suggests that as academic stress increases, coping self-efficacy decreases. Further, being a female, SHS2, and in the HUMSS strandtends to increase academic stress, while being a female who is unemployed and/or a mother whose working at home scores relatively low with coping self-efficacy.Significance – These findings have educational implications. It highlights the factors to be considered by offering guidance to counselors and educators in developing intervention programs, focusing on psychological well-being and skill enhancement that would help mitigate the adverse outcomes of this period of disruption.